Determinants of Banks Rentability Listed on The Indonesia Stock Exchage (IDX) Period 2016-2019 - Dwi Endah Pratiwi; Anindya Ardiansari (Universitas Negeri Semarang, 2022)
The main purpose of this study to analyze the effect of CAR, LDR, LTA, SRR, NPL, OC and GDP on bank rentability (ROA). Population in this study are all companies is the banking sub-sector listed on the Indonesia Stock Exchange period 2016-2019. The sampling method used purposive sampling, resulting in a sample of 27 companies. This study using multiple linear regression analysis with Eviews 9 software as an analytical tool. The results showed that CAR had positive and insignificant effect on ROA, LDR had positive and insignificant effect on ROA, LTA had positive and insignificant effect on ROA, SRR had negative and insignificant effect on ROA, NPL had negative and significant effect on ROA, OC had negative and significant effect on ROA, and GDP has negative and significant effect on ROA.